Inflation Targeting and Unemployment in the South African Retail Sector - Mutwanamba, Pfarelo Victor (University of the Witwatersrand, Johannesburg, 2024)
This study investigates the impact of inflation targeting on employment in the South Africanretail sector, addressing concerns from trade unions and stakeholders regarding the nation'smonetary policy framework. Spanning from 2000 to 2022, coinciding with the adoption ofinflation targeting by the South African Reserve Bank (SARB) in year 2000, the researchutilises econometric methods and secondary data to fill gaps in the literature, notably the lackof dedicated research on the retail sector and the mechanisms through which inflationtargeting influences retail sector employment. Amidst persistent developmental challenges,including a 32.7% unemployment rate in Q4 2022, heightened poverty and inequality (i.e.,South Africa has the highest Gini Coeffient1 in the world), and sluggish economic growth, thestudy uncovers nuanced insights. While inflation targeting measures contribute to pricestability, they do not directly address the underlying structural issues contributing to elevatedunemployment rates. This aligns with the formulated hypotheses that (H1) the implementationof SARB's inflation targeting framework has a significant impact on employment in SouthAfrica's retail industry, and (H2) the approach adopted by the SARB in implementing itsinflation targeting policy influences the extent of its impact on employment in South Africa'sretail industry – implying that the null hypothesis (H0) is rejected in favour of alternativehypotheses. The study's conclusion, substantiated by Johansen Cointegration, GrangerCausality, and Impulse Functions analyses, affirms the substantial impact of SARB's inflationtargeting framework on retail sector employment. The Johansen Cointegration analysisestablishes a stable, statistically significant long-term relationship between interest rates andretail employment, corroborating the hypotheses. Furthermore, the study highlights thenecessity for targeted policy interventions, such as enhanced skills training programs andsupport for small and medium-sized enterprises (SMEs). Additionally, it emphasises theimportance of tailored responses to effectively address unemployment and promotesustainable economic development in South Africa. Notably, the study suggests an expandedrole for SARB beyond its mandate of price stability, endorsing proactive measures to tacklethe structural issues contributing to unemployment in the retail sector
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Inflation Targeting Framework; Monetary Policy; Repo Rate; Lending Rate; Unemployment; SDG-8: Decent work and economic growth